2013
DOI: 10.1111/trf.12124
|View full text |Cite
|
Sign up to set email alerts
|

If the permanent deferral were lifted would men who have sex with men want to donate blood, and if so, who would be eligible?

Abstract: The majority of MSM are interested in donating blood. Depending on how the policy would be changed (i.e., either a temporary or a behavior-based deferral criterion), substantial numbers of MSM would be eligible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 14 publications
2
25
4
Order By: Relevance
“…Our findings are similar to two previous studies that found donation rates among MSM who did not meet deferral criteria to be 23.4 and 42%. 3,15 While the adoption of a 12-month deferral period represented a major policy shift for the United States, other nations, such as Japan, Finland, Sweden, the Netherlands, France, the United Kingdom, Australia, and New Zealand, have previously adopted 12-month or shorter deferral policies. Interestingly, several socially progressive countries, such as Denmark, Iceland, and Norway, as well as Austria, Germany, and Belgium, still maintain a lifetime deferral.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to two previous studies that found donation rates among MSM who did not meet deferral criteria to be 23.4 and 42%. 3,15 While the adoption of a 12-month deferral period represented a major policy shift for the United States, other nations, such as Japan, Finland, Sweden, the Netherlands, France, the United Kingdom, Australia, and New Zealand, have previously adopted 12-month or shorter deferral policies. Interestingly, several socially progressive countries, such as Denmark, Iceland, and Norway, as well as Austria, Germany, and Belgium, still maintain a lifetime deferral.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1980s, exclusion of MSM from blood donation has been denounced by gay men, who were frequent blood donors prior to the ban and are still interested in donating blood . At a time when gay men still faced extensive prejudice, establishing a link between being gay and spreading HIV and thus being excluded as a group from a valued social practice was seen as discriminatory.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 42.0% of participants admitted to donating blood. Although this is nearly twice as much as the 23.4% of MSMs who admitted to donating blood in a survey performed in San Francisco, both studies demonstrate that MSMs are donating blood despite the lifetime deferral. Similarly, 85.9% of our participants, and 77.3% of the MSMs from the San Francisco study, would be willing to donate blood if the lifetime deferral were changed.…”
Section: Discussionmentioning
confidence: 77%
“…Although this is nearly twice as much as the 23.4% of MSMs who admitted to donating blood in a survey performed in San Francisco, both studies demonstrate that MSMs are donating blood despite the lifetime deferral. Similarly, 85.9% of our participants, and 77.3% of the MSMs from the San Francisco study, would be willing to donate blood if the lifetime deferral were changed. Interestingly, a recent model in England and Wales found a minimal risk in switching from a lifetime to a 5‐year deferral .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation